Development of Maritime Area Resilience in The Indonesian Border Areas As Implementation of A Total War Strategy in Peace Times - Samsul Bahri Wahidun; Edy Sulistyadi; Buddy Suseto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Building maritime regional resilience in Indonesia's border areas is a crucial aspect in maintaining national sovereignty and security. Against the background of the potential threats faced, this strategy aims to strengthen Indonesia's position as a maritime country. Implementation of a total war strategy in peacetime emphasizes the mobilization of national resources, improving infrastructure and strengthening international cooperation, apart from that through modernizing the main weapons system (alutsista) so that maritime resilience can be significantly improved. The method used in writing this journal uses a qualitative method with a descriptive analysis approach, which aims to interpret existing phenomena. Writing this journal also highlights the important role of society in maintaining maritime security and the need for a sustainable approach in managing marine resources. It is hoped that the results of this development will create sustainable stability and security in border areas and can support Indonesia's vision as the world's maritime axis.